Treatment of Acute Achilles Tendon Ruptures: A Systematic Review of Overlapping Meta-Analyses. Issue 4 (November 2022) - Seow, Dexter; Ubillus, Hugo A.; Azam, Mohammad T.; Weiss, Matthew B.; Gianakos, Arianna L.; Yasui, Youichi; Pearce, Christopher J.; Kennedy, John G.
Category: Ankle Introduction/Purpose: Acute Achilles tendon rupture (AATR) is a common injury of an incidence rate of up to 31 per 100, 000 per year. The current meta-analyses on the treatment of AATR have conflicted data that may, in part, be due to the differences in their methodologies. The aim of this study is to systematically review and present the current meta-analyses for the treatment of AATR. The outcomes of this study can provide clinicians with a clear overview of the current literature to help decide on the optimal treatment for patients. Methods: Two independent reviewers searched PubMed and Embase on March 17, 2020 based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Assessment of evidence was two-fold: level of evidence (LoE) and quality of evidence (QoE). LoE was evaluated using published criteria by The Journal of Bone and Joint Surgery and the QoE by the Assessing the Methodological Quality of Systematic Reviews (AMSTAR) scale. Pooled complication rates were highlighted for significance in favor of 1 group or no significance. Statistical analysis was performed using a statistical software package (R version 3.5.1; R Foundation for Statistical Computing, Vienna, Austria). Descriptive statistics were calculated for each study and statistical parameters analyzed. Continuous variables were reported as mean +- standard deviation and categorical variables were reported as frequencies with percentages. P-values < 0.05 was considered statistically significant. Results: 21 meta-analyses were included in the study. Re-rupture rates ranged between 2.3% to 5.0% for open repair/MIS and 3.9% to 13% for conservative treatment (p < 0.05). Re-rupture rates were reported in 3 of 4 meta-analyses that ranged between 2.3% to 7.8% for conservative treatment earlier rehabilitation and 5.0% to 12.2% for conservative treatment later rehabilitation. Re-rupture rates were 2.5% for open repair earlier rehabilitation and 3.8% for open repair later rehabilitation. When comparing surgical techniques, re-rupture rates ranged between 1.4% to 3.1% for percutaneous repair/MIS and 2.2% to 2.7% for open repair. Infection rates ranged between 2.8% to 5.0% for open repair/MIS and 0% to 0.02% for conservative treatment. The majority of meta-analyses (3 of 5) significantly favored by effect size, open repair/MIS for total infection rates (p < 0.05). Conclusion: The results of this study demonstrate that operative repair reduced the rate of re-rupture when compared to conservative treatment. There is currently conflicting information on whether early functional rehabilitation reduces the difference between the two treatments. Operative treatment has been shown to have a higher rate of wound complications, although the rates of deep wound infections remains to be determined. Percutaneous repair resulted in similar re-rupture rates when compared to open surgery but for the rates of other complications including wound infections, this was diminished. Further meta- analyses which compare all cohorts are needed to ascertain best evidence.